The coupling between the dissolution of the old social pact and the emergence of new technologies in the (resistible) path toward the abyss - Giovanni Dosi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2025)
There are at least three existential challenges to contemporary societies, as we know them namely first, the complete rupture of the social pact which characterized Glorious Decades after WWII in most of Western societies; and second, the deepening of the patterns of informatization and "intelligent" automation with the associated modifications in labour relations and mechanisms of social control . All that, third, is coupled with a climate crisis that might have well reached a tipping point toward a global ecological disaster. Here I shall briefly discuss the first , and even more briefly the second one , ending with some urgent policy implications.
Keywords: 330; Social Conflict; Social Pact; Inequality; Artificial Intelligence and Labour Processes; Environmental Crisis; Policy Objectives